Swedish Pharmacy Students' Expectations and Perceptions of Their Education and Future Pharmacy Profession - Maria Gustafsson; Sofia Mattsson (MDPI AG, 2019)
Distance education is becoming more and more common, and today distance education is well established within academic settings. The aim was to investigate first-year pharmacy students’ expectations and perceptions of web-based pharmacy programs and of their future profession. Furthermore, student characteristics were compared over time. A questionnaire was distributed to all first-year students admitted to the pharmacy programs at Umeå University in 2017. The students were asked questions about their background, motives for choosing pharmacy education, and their expectations and perceptions of their education and profession. Factors of most importance when choosing the education were: the education is interesting, leads to an interesting job, and is web-based. The students’ expectations of the education were high, and they want to learn as much as possible and be well prepared for their future profession. Regarding the students’ perception of their future profession, three themes were identified: to help other people, professional development, and employment related issues. Student characteristics have changed over the years, suggesting that the web-based pharmacy education and the flexibility it entails attracts other groups of students today compared with when the programs started.